Utilizing Organoid and Air-Liquid Interface Models as a Screening Method in the Development of New Host Defense Peptides - Choi, Ka-Yee Grace; Wu, Bing Catherine; Lee, Amy Huei-Yi; Baquir, Beverlie; Hancock, Robert E. W. (Frontiers in Cellular and Infection Microbiology, 2020)
Host defense peptides (HDPs), also known as antimicrobial peptides, are naturally occurring polypeptides (~12–50 residues) composed of cationic and hydrophobic amino acids that adopt an amphipathic conformation upon folding usually after contact with membranes. HDPs have a variety of biological activities including immunomodulatory, anti-inflammatory, anti-bacterial, and anti-biofilm functions. Although HDPs have the potential to address the global threat of antibiotic resistance and to treat immune and inflammatory disorders, they have yet to achieve this promise. Indeed, there are several challenges associated with bringing peptide-based drug candidates from the lab bench to clinical practice, including identifying appropriate indications, stability, toxicity, and cost. These challenges can be addressed in part by the development of innate defense regulator (IDR) peptides and peptidomimetics, which are synthetic derivatives of HDPs with similar or better efficacy, increased stability, and reduced toxicity and cost of the original HDP. However, one of the largest gaps between basic research and clinical application is the validity and translatability of conventional model systems, such as cell lines and animal models, for screening HDPs and their derivatives as potential drug therapies. Indeed, such translation has often relied on animal models, which have only limited validity. Here we discuss the recent development of human organoids for disease modeling and drug screening, assisted by the use of omics analyses. Organoids, developed from primary cells, cell lines, or human pluripotent stem cells, are three-dimensional, self-organizing structures that closely resemble their corresponding in vivo organs with regards to immune responses, tissue organization, and physiological properties; thus, organoids represent a reliable method for studying efficacy, formulation, toxicity and to some extent drug stability and pharmacodynamics. The use of patient-derived organoids enables the study of patient-specific efficacy, toxicogenomics and drug response predictions. We outline how organoids and omics data analysis can be leveraged to aid in the clinical translation of IDR peptides.